A study of company strategies in the telecommunications industry : effect of incumbency on company performance - Pang, Elaine Yi Ping (2008)
Our FYP is a study on the telecommunications industry where new firms continually emerge. Some overtake incumbents while others remain within their niches. We explore the mobile cellular market particularly, to determine whether the incumbents enjoy certain advantages over new entrants.